An overview of simple and complex test setups for experimental assessment of masonry structures concerning seismic behaviour - Alexandre A. Costa (2009)
Several different experimental test techniques can be used to assess the behavior of masonry structures for a wide range of objectives (vertical capacity, lateral load, seismic behavior, etc.). In such context, this paper presents several setups considered from the simplest one for in-situ use, to more complex ones used in laboratory conditions. Some examples are presented as used to characterize the expected seismic response through in-plane and out-of-plane tests on masonry walls adopting simple in-situ or complex laboratory setups. Among these examples, two new test setups developed for in-situ assessment of existing structures are presented where good results were obtained. Finally, some comments are included regarding the efficiency of simple test schemes when compared to more complex and elaborated test setups as well as the applicability of the later to in-situ or laboratory conditions regarding costs, time and the requirements for their use. The paper content is expected to help researchers on choosing the suitable testing option for each particular experiment.